Socio-Economic Potential Of Fishermen In Pulau Banyak, Aceh Singkil - Amarullah, Teuku; Rahmawati, Rahmawati; Zuraidah, Syarifah; Zuriat, Zuriat (Politeknik Ahli Usaha Perikanan, 2023)
Communities in Pulau Banyak District on average work in the fisheries sector as fishers. Pulau Banyak fishers take advantage of the potential of captured fisheries as their main source of income. The living conditions of fishers are often classified as a marginal group close to poverty. This study aims to examine the socio-economic conditions of fishers in the Pulau Banyak District of Aceh Singkil. The method used is to conduct a field survey using a questionnaire (interview). The location of the research was in Pulau Banyak District, Aceh Singkil Regency. The results of the study show that the social conditions of the Pulau Banyak people work as fishers with a low level of education, at most equivalent to elementary school. The economic condition of the fishers on Pulau Banyak is seen based on their main income and also other income sourced from side income and the income of family members who help fishers. The main source of income for fishers is an average of IDR 1,000,000-1,500,000 per month with an average trip of 6 times a week or 24 times a month with catches of 8 types of fish. While the pattern of fish marketing, the average fishers as much as 64 percent choose to sell to bench shops. The government has an important role in monitoring the marketing pattern of fishery products and implementing policies for optimal and sustainable utilization of fishery resources.